Guidance for the design and application of shoulder and centerline rumble strips - Torbic, Darren J. (Report (National Cooperative Highway Research Program) ;, 2009)
This report provides guidance for the design and application of shoulder and centerline rumble strips as an effective crash reduction measure, while minimizing adverse effects for motorcyclists, bicyclists, and nearby residents. Using the results of previous studies and the research conducted under this project, safety effectiveness estimates were developed for shoulder rumble strips on rural freeways and rural two-lane roads and for centerline rumble strips on rural and urban two-lane roads.